Supine percutaneous nephrolithotomy and ECIRS : the new way of interpreting PNL - Scoffone, Cesare Marco; Hoznek, Andras; Cracco, Cecilia Maria; Scoffone, Cesare Marco (Springer Paris, 2014)
PNL is the gold standard for the management of large and/or otherwise complex renal stones. Since its introduction in the seventies PNL has undergone considerable evolution, mainly driven by the improvement in access techniques, endoscopic instrument technology, lithotripsy devices and drainage management. The conventional prone position for PNL has been challenged in the last two decades by a variety of modifications, including the supine and Galdakao-modified supine Valdivia positions, which make simultaneous retrograde working access to the collecting system possible and have proven anesthesiological advantages. The Galdakao-modified supine Valdivia position allowed the development of ECIRS (Endoscopic Combined IntraRenal Surgery), a technique exploiting a combined antegrade and retrograde approach to the upper urinary tract, using both rigid and flexible endoscopes with the related accessories. The synergistic teamwork of ECIRS provides a safe and efficient, minimally-invasive procedure for the treatment  of all kinds of urolithiasis. The aim of this book is to share with the urologic community worldwide our experience, our standardization of all the steps, and tips and tricks for the procedure.